1998
DOI: 10.1183/09031936.98.12040960
|View full text |Cite
|
Sign up to set email alerts
|

New bioelectrical impedance formula for patients with respiratory insufficiency: comparison to dual-energy X-ray absorptiometry

Abstract: Severe respiratory insufficiency causes patients to be intolerant of physical effort and to be frequently limited in their daily activity and results in an imbalance between food intake and nutritional needs. Undernutrition and overnutrition can both affect the quality of life and survival of patients with pulmonary disease. Protein-energy malnutrition can lead to quantitative, qualitative and functional alterations of muscle [1,2] and this affects muscle function, including respiratory muscle in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
58
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 36 publications
4
58
0
4
Order By: Relevance
“…By contrast to their original equation, this provides sex-specific equations for COPD patients and may explain why the agreement between BIA and DEXA is better in the present study than in that of PICHARD et al [16]. More recently, a prediction equation for COPD patients using DEXA as a reference method has been published [18]. Perhaps not surprisingly (as the equation used was derived from data within the study), the limits of agreement between DEXA and BIA reported in this latter study were narrower than in the present one.…”
Section: Discussionmentioning
confidence: 58%
“…By contrast to their original equation, this provides sex-specific equations for COPD patients and may explain why the agreement between BIA and DEXA is better in the present study than in that of PICHARD et al [16]. More recently, a prediction equation for COPD patients using DEXA as a reference method has been published [18]. Perhaps not surprisingly (as the equation used was derived from data within the study), the limits of agreement between DEXA and BIA reported in this latter study were narrower than in the present one.…”
Section: Discussionmentioning
confidence: 58%
“…12 Exercise capacity was evaluated with 3 tests: the 6-min walk test, 13 with the reference values from Troosters et al 14 ; incremental symptom-limited cycle ergometry, 15 following a program previously described 16 ; and constant-workcycle ergometry (endurance time). Body composition was assessed with bioelectrical impedance 17 and we used the specific values described by Kyle et al 18 Respiratory muscle force was measured with the maximum inspiratory and expiratory pressures, 19 with the reference values from Neder et al 20 Peripheral muscle force was assessed with the onerepetition maximum test. Functional status was assessed with the London Chest Activity of Daily Living (LCADL) scale 21 and the Pulmonary Functional Status and Dyspnea Questionnaire Modified Version (PFSDQ-M).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…Body composition was evaluated by bioelectrical impedance (BIA 101A; RJL systems, USA) according to the guidelines of the European Society for Parenteral and Enteral Nutrition (ESPEN) (12). Fat-free mass (FFM, kg) was calculated using a group-specific regression equation developed by Kyle et al (13). The FFM index (FFMI = FFM/height 2 ) was also calculated.…”
Section: Nutritional Assessmentmentioning
confidence: 99%